2012
DOI: 10.1111/j.1476-5381.2012.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H4 receptor antagonists as potent modulators of mammalian vestibular primary neuron excitability

Abstract: BACKGROUND AND PURPOSEBetahistine, the main histamine drug prescribed to treat vestibular disorders, is a histamine H3 receptor antagonist. Here, we explored the potential for modulation of the most recently cloned histamine receptor (H4 receptor) to influence vestibular system function, using a selective H4 receptor antagonist JNJ 7777120 and the derivate compound JNJ 10191584. EXPERIMENTAL APPROACHRT-PCR was used to assess the presence of H4 receptors in rat primary vestibular neurons. In vitro electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Moreover, JNJ 10191584 and JNJ 7777120 ameliorated the symptoms in two different rat models of vestibular deficits (3,3 0 -iminodipropionitrile injection and kainate-induced unilateral excitotoxic insult) (Desmadryl et al, 2012). Furthermore, H 4 R mRNA was detected in the vestibular ganglion of rats by RT-PCR (Desmadryl et al, 2012).…”
Section: Moreover [ 35 S]gtpgs ([ 35 S]guanosine 5'-[g-thio]triphospmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, JNJ 10191584 and JNJ 7777120 ameliorated the symptoms in two different rat models of vestibular deficits (3,3 0 -iminodipropionitrile injection and kainate-induced unilateral excitotoxic insult) (Desmadryl et al, 2012). Furthermore, H 4 R mRNA was detected in the vestibular ganglion of rats by RT-PCR (Desmadryl et al, 2012).…”
Section: Moreover [ 35 S]gtpgs ([ 35 S]guanosine 5'-[g-thio]triphospmentioning
confidence: 97%
“…A publication by Desmadryl et al (2012) attracted some interest, because it reported that the selective H 4 R antagonists JNJ 10191584 and JNJ 7777120 reduced the electrically evoked discharge volley of primary vestibular neurons in a reversible, 4-MH-sensitive and concentration-dependent manner (Desmadryl et al, 2012). Moreover, JNJ 10191584 and JNJ 7777120 ameliorated the symptoms in two different rat models of vestibular deficits (3,3 0 -iminodipropionitrile injection and kainate-induced unilateral excitotoxic insult) (Desmadryl et al, 2012).…”
Section: Moreover [ 35 S]gtpgs ([ 35 S]guanosine 5'-[g-thio]triphospmentioning
confidence: 97%
See 1 more Smart Citation
“…mRNA expression of both the full-length H 4 receptor and one of the deletion forms has also been detected in a rat brain endothelial cell line using reversetranscription polymerase chain reaction and sequencing (Karlstedt et al, 2013). The H 4 receptor may also be involved in the vestibular system, because expression of the receptor has been reported in vestibular nucleus neurons and ganglia in rats (Desmadryl et al, 2012;Zhang et al, 2013). Overall, the presence of the H 4 receptor in afferent pathways including dorsal root ganglion, spinal cord dorsal horn, and thalamus, as well as in other CNS areas, appears to be entirely consistent with a role in sensory signaling.…”
Section: Anatomic Frameworkmentioning
confidence: 97%
“…In whole cell clamp recordings of layer IV somatosensory cortex cells from mice, H 4 receptor-induced hyperpolarization has been reported with a single H 4 receptor agonist, antagonist, and respective dose (Connelly et al, 2009); confirmation is required with multiple ligands and a full concentration range. In rat vestibular neurons, treatment H 4 receptor antagonist led to inhibitory effects on the action potential (Desmadryl et al, 2012). In addition it has been shown that the receptor also mediated action potential discharge in human submucosal neurons (Breunig et al, 2007).…”
Section: Functionmentioning
confidence: 99%